Problems and Resolutions of Traditional Land Disputes in the Minangkabau Region - Rahmat, Doris; Budi NU, Santoso; Reviando, Yohanes (Yayasan Kawanad, 2024)
The Indonesian Constitution recognizes indigenous legal communities as part of the wealth of the Unitary State of the Republic of Indonesia whose existence and rights are guaranteed. One such group is the Minangkabau community, which is often involved in customary land ownership disputes. Internal and external conflicts in society. Many things cause these conflicts: non-transparent deliberation processes, lack of openness in the termination of customary land, inadequate compensation, and lack of guarantees from private companies. This study uses a descriptive empirical legal approach with primary data sourced from the field. Disputes are resolved through customary procedures, which usually involve the implementation of customary systems, deliberation, consensus through negotiation or mediation between local customs and companies (or representing companies) → Formulation of customary land disputes. Then the decision is formalized by registering the agreement with a notary or court so that it can be [legally] enforced. However, dispute resolution can be facilitated by a third party, for example, the territorial government approach that provides support in negotiations or finding agreements